Computer systems architecture - Yadin, Aharon (Chapman & Hall/CRC textbooks in computing, 2016)
The book describes trends in computing solutions that led to the current available infrastructures, tracing the initial need for computers to recent concepts such as the Internet of Things. It covers computers' data representation, explains how computer architecture and its underlying meaning changed over the years, and examines the implementations and performance enhancements of the central processing unit (CPU). It then discusses the organization, hierarchy, and performance considerations of computer memory as applied by the operating system and illustrates how cache memory significantly improves performance